Reassessing customer trust and privacy concerns in omnichannel customer experience - Hadiqa Riaz; Hassaan Ahmed; Abdul Bashiru Jibril (Cogent Business & Management, 2024)
In today's retail landscape, omnichannel customer experience plays a crucial role in fostering long-term customer trust and satisfaction. However, there remains a gap in understanding the precise impact of omnichannel experiences on these key factors. This research addresses this gap by examining how each dimension of the omnichannel customer experience influences customer trust and satisfaction. Additionally, it investigates the mediating role of customer trust in the relationship between omnichannel experience and satisfaction. Moreover, considering the growing concerns surrounding privacy in the context of retail technology, this study explored the moderating effect of privacy concerns on these relationships. Data from 300 omnichannel customers were collected using purposive sampling and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings support previous conceptualizations, indicating that all dimensions of omnichannel customer experience, except connectivity, positively impact customer trust. Furthermore, customer trust was found to mediate the relationship between omnichannel experience and satisfaction, with the exception of connectivity. Additionally, the study reveals that customer privacy concerns moderate the relationship between connectivity and trust as well as between channel integration and trust. These findings offer practical insights for omnichannel retailers to enhance channel management, thus improving the overall shopping experience and customer satisfaction. Moreover, this research underscores the importance of addressing privacy concerns to bolster customer trust. By shedding light on these dynamics, this study contributes to the existing literature and provides guidance for retailers aiming to cultivate a loyal and satisfying customer base in the omnichannel era.
Keywords: 650; Omnichannel; customer experience; customer trust; privacy concern; customer satisfaction